Diabetic Neuropathy: Mechanisms, Emerging Treatments, and Subtypes - Albers, James W. (Curr Neurol Neurosci Rep, 2014)
Diabetic neuropathies (DNs) differ in clinical course, distribution, fiber involvement (type and size), and pathophysiology, the most typical type being a length-dependent distal symmetric polyneuropathy (DSP) with differing degrees of autonomic involvement. The pathogenesis of diabetic DSP is multifactorial, including increased mitochondrial production of free radicals due to hyperglycemia-induced oxidative stress. Mechanisms that impact neuronal activity, mitochondrial function, membrane permeability, and endothelial function include formation of advanced glycosylation end products, activation of polyol aldose reductase signaling, activation of poly(ADP ribose) polymerase, and altered function of the Na(+)/K(+)-ATPase pump. Hyperglycemia-induced endoplasmic reticulum stress triggers several neuronal apoptotic processes. Additional mechanisms include impaired nerve perfusion, dyslipidemia, altered redox status, low-grade inflammation, and perturbation of calcium balance. Successful therapies require an integrated approach targeting these mechanisms. Intensive glycemic control is essential but is insufficient to prevent onset or progression of DSP, and disease-modifying treatments for DSP have been disappointing. Atypical forms of DN include subacute-onset sensory (symmetric) or motor (asymmetric) predominant conditions that are frequently painful but generally self-limited. DNs are a major cause of disability, associated with reduced quality of life and increased mortality.